Routledge handbook of sports coaching - Potrac, Paul 1974-; Gilbert, Wade; Denison, Jim 1963- (Routledge, 2014)
This title survey the full depth and breadth of contemporary coaching studies, mapping the existing disciplinary territory and opening up important new areas of research. Bringing together many of the world's leading coaching scholars and practitioners working across the full range of psychological, social and pedagogical perspectives, the book helps to develop an understanding of sports coaching that reflects its complex, dynamic and messy reality.